Advanced system demonstration for utilization of biomass as an energy source (Wood Energy Inst., Camden, ME (USA), 1980)
The results of a 20 month study to explore the technical and economic feasibility of fuelwood utilization to operate a 50 megawatt energy conversion facility are described. The availability of biomass as a fuel source, the methods of harvesting and collecting the fuelstock, the costs of providing adequate fuel to the plant, and other requirements for fueling the proposed conversion facility are investigated. (MHR)